2004
DOI: 10.1073/pnas.0404817101
|View full text |Cite
|
Sign up to set email alerts
|

Metastability of Helicobacter pylori bab adhesin genes and dynamics in Lewis b antigen binding

Abstract: Heterogeneity amongbabA genes, babA1 (silent) and babA2 (expressed). We found that a babA2-cam derivative of strain 17875 regained Leb binding by recombination of the formerly silent babA1 gene into the expressed and partially homologous babB locus. The chimeric BabB͞A adhesin binds Leb with an affinity similar to that of wild-type BabA adhesin, but its expression level was lower and was subject to phase variation through slipped-strand mispairing. Equivalent results were obtained with strain NCTC11638. We pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
108
2
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(115 citation statements)
references
References 31 publications
4
108
2
1
Order By: Relevance
“…However, we were unable to confirm any relationship between the number of adenine residues within the −10 to −35 region and BabA status ( Figure 4). Although previous reports have suggested that chimeric babA/B or babB/A points were located close to the start codon, 24,25 we did not detect any chimeric formation within the region 600 bp from the start codon (data not shown).…”
Section: Sequencing Of the Promoter And Signal Region Of The Baba Genecontrasting
confidence: 41%
See 3 more Smart Citations
“…However, we were unable to confirm any relationship between the number of adenine residues within the −10 to −35 region and BabA status ( Figure 4). Although previous reports have suggested that chimeric babA/B or babB/A points were located close to the start codon, 24,25 we did not detect any chimeric formation within the region 600 bp from the start codon (data not shown).…”
Section: Sequencing Of the Promoter And Signal Region Of The Baba Genecontrasting
confidence: 41%
“…24,25 This region is stable when the number of adenines was 14, but would become nonfunctional when the number was reduced to 10. 24 The number of adenine residues was 8 -14 in the strains we analyzed. However, we were unable to confirm any relationship between the number of adenine residues within the −10 to −35 region and BabA status ( Figure 4).…”
Section: Sequencing Of the Promoter And Signal Region Of The Baba Genementioning
confidence: 99%
See 2 more Smart Citations
“…Adherence of H. pylori to the gastric epithelium is a complicated process that involves a number of bacterial cell-surface receptors, including the Lewis B-bind- ing (Le b -binding) adhesin BabA (34), an outer membrane protein encoded by babA2 that binds the histo-blood group antigen Le b on the surface of epithelial cells. Even H. pylori strains that do not bind Le b usually possess silent babA gene sequences that can be activated by recombination events (35). Infection with H. pylori strains containing babA2, cagA, and the vacuolating cytotoxin (Vac) allele vacAS1 confers the highest risk of gastric cancer (36).…”
Section: Role Of Bacterial Virulence Factors In H Pylori Persistencementioning
confidence: 99%